Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.measurement.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Application of two-output port fiber coupler as gasoline level sensor

Abstract: Novel dynamic balance test is sensitive to alpine skier's expertise level.Application of cross correlation method for analysing rhythmic COP movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The z 01 and z 02 values are of the same magnitude of 7.7 mm. As in previous studies [10,11], the use of membranes as a sensor component causes the sensor output characteristics to produce hysteresis. The nature of the membrane relaxation after the pressure is the cause of the hysteresis.…”
Section: Areamentioning
confidence: 69%
See 2 more Smart Citations
“…The z 01 and z 02 values are of the same magnitude of 7.7 mm. As in previous studies [10,11], the use of membranes as a sensor component causes the sensor output characteristics to produce hysteresis. The nature of the membrane relaxation after the pressure is the cause of the hysteresis.…”
Section: Areamentioning
confidence: 69%
“…Optical devices based on optical fiber have been widely developed to detect liquid level. These devices including fiber Bragg gratings [1][2][3], photonic crystal fiber [4], fiber bundle [5,6], and fiber coupler [7,10,11]. The working principle of fiber Bragg grating and photonic crystal fiber is based on wavelength modulation in detecting liquid level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection is performed by moving the probe to find the presence of liquid due to the probe interaction with the liquid will change the intensity of the reflected light received by the fiber bundle. Based on the displacement sensor and utilizing the principle of hydrostatic pressure, we have developed liquid (gasoline) level sensor using an output port as well as two output ports fiber coupler …”
Section: Introductionmentioning
confidence: 99%
“…Based on the displacement sensor and utilizing the principle of hydrostatic pressure, we have developed liquid (gasoline) level sensor using an output port 7 as well as two output ports fiber coupler. 8 Research results have shown that fiber coupler, 9 a pair, 10 and concentric 11 bundled probe can be applied as a displacement sensor. Based on displacement sensor and using the principle of hydrostatic pressure, in this article, liquid level sensor is demonstrated using fiber coupler, a pair, and concentric bundled probes in the same experimental condition.…”
Section: Introductionmentioning
confidence: 99%